2016
DOI: 10.1111/bjd.14674
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body reaction triggered by cytotoxic T lymphocyte-associated protein 4 blockade 25 years after dermal filler injection

Abstract: Foreign body reactions are regularly seen as a late complication of cosmetic treatment with synthetic dermal fillers. Often this foreign body reaction is triggered by a systemic infection, but other systemic triggers are also reported. In this case report, we present a woman in her 60s who was treated with ipilimumab for metastatic melanoma. After two courses of treatment she developed painless facial nodules. A foreign body reaction to dermal fillers was suspected because the patient had received cosmetic tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Bisschop et al reported a case of malignant melanoma treated with ipilimumab in which the patient developed a foreign body granulomatous reaction during immunotherapy 25 years after the injection of permanent synthetic fillers. 9 A reaction thought to be precipitated by activation of the adaptive immune system during cytotoxic T lymphocyte-associated protein-4 blockade. Given the ever-increasing use of both checkpoint inhibitors and cosmetic fillers this may represent the first of many such cases.…”
Section: Postulate Insights Into Disease Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Bisschop et al reported a case of malignant melanoma treated with ipilimumab in which the patient developed a foreign body granulomatous reaction during immunotherapy 25 years after the injection of permanent synthetic fillers. 9 A reaction thought to be precipitated by activation of the adaptive immune system during cytotoxic T lymphocyte-associated protein-4 blockade. Given the ever-increasing use of both checkpoint inhibitors and cosmetic fillers this may represent the first of many such cases.…”
Section: Postulate Insights Into Disease Pathophysiologymentioning
confidence: 99%
“…6 HS is associated with elevated body mass index with obesity possibly contributing to HS disease severity. 7 The patient 5 The treatment of hidradenitis suppurativa with the glucagon-like peptide-1 agonist liraglutide 6 Describe new adverse effects of therapies Vemurafenib-induced toxic epidermal necrolysis: possible cross-reactivity with other sulfonamide compounds 8 Foreign body reaction triggered by cytotoxic T lymphocyte-associated protein 4 blockade 25 years after dermal filler injection 9 Paradoxical ulcerative colitis during adalimumab treatment of psoriasis 10 Lichenoid drug eruption induced by an infliximab biosimilar 11…”
mentioning
confidence: 99%
“…In their case report, Bisschop et al . describe a patient in whom ipilimumab elicited a typical granulomatous reaction, necessitating surgical removal of inflammatory nodules . The filler compound (most probably silicone oil) mentioned in this case belongs to a group of minimally biodegradable filler products, known to have a notoriously high incidence of resultant immunological reactions…”
mentioning
confidence: 97%
“…The clearly written case report by Bisschop et al ., in this issue of the BJD , describes a granulomatous reaction as a late complication of a minimally biodegradable filler . This foreign body reaction triggered by a cytotoxic T‐lymphocyte‐associated (CTLA)‐4 blocking monoclonal antibody was seen decades after the probable injection of silicone oil as a soft tissue filler.…”
mentioning
confidence: 99%
“…We interpret the subcutaneous FDG uptake as a nivolumab-related foreign body reaction to the dermal filler. Foreign body reactions following dermal filler can be triggered by systemic infections, drugs or immunotherapy [2][3][4]. One case report describes a foreign body reaction during ipilimumab for malignant melanoma [2], but to date there are no reports of comparable reactions during nivolumab.…”
mentioning
confidence: 99%